2014
DOI: 10.1073/pnas.1307712111
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying causal mechanisms to determine how protected areas affect poverty through changes in ecosystem services and infrastructure

Abstract: To develop effective environmental policies, we must understand the mechanisms through which the policies affect social and environmental outcomes. Unfortunately, empirical evidence about these mechanisms is limited, and little guidance for quantifying them exists. We develop an approach to quantifying the mechanisms through which protected areas affect poverty. We focus on three mechanisms: changes in tourism and recreational services; changes in infrastructure in the form of road networks, health clinics, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
181
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 252 publications
(188 citation statements)
references
References 41 publications
2
181
1
4
Order By: Relevance
“…Conservation actions can improve human welfare through various mechanisms, including the maintenance and enhancement of ecosystem services. A recent study of these mechanisms could only estimate how protected areas affected poverty through changes in land cover, rather than through changes in specific services that arose from the changes in land cover (54). Future attempts to quantify these mechanisms could benefit from more careful and rigorous connections to the modeling and monetization literature.…”
Section: Discussionmentioning
confidence: 99%
“…Conservation actions can improve human welfare through various mechanisms, including the maintenance and enhancement of ecosystem services. A recent study of these mechanisms could only estimate how protected areas affected poverty through changes in land cover, rather than through changes in specific services that arose from the changes in land cover (54). Future attempts to quantify these mechanisms could benefit from more careful and rigorous connections to the modeling and monetization literature.…”
Section: Discussionmentioning
confidence: 99%
“…Such temporal analyses are required to identify whether it is indeed forest-related provisioning ES that are leading to poverty alleviation, or whether the higher incomes in non-poor counties stem from non-consumptive ES like tourism (e.g. Ferraro and Hanauer 2014) or other non-ESderived incomes sources.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental (Jayachandran et al 2016) and quasi-experimental (Alix-Garcia et al 2012) studies have found that payments for ecosystem services (PES) programs in Uganda and Mexico, respectively, were eff ective in avoiding deforestation. IE studies have also increasingly sought to identify causal mechanisms linking the intervention to ultimate impacts (e.g., Canavire-Bacarreza and Hanauer 2013; Ferraro and Hanauer 2014;Ferraro and Pressey 2015). Th ese studies have begun to explore what happens within the "black box" of program and policy implementation that leads to observed outcomes at the end of the program period.…”
Section: Experimental and Quasi-experimental Impact Evaluation Approamentioning
confidence: 99%
“…Th ese studies have begun to explore what happens within the "black box" of program and policy implementation that leads to observed outcomes at the end of the program period. For instance, Paul Ferraro and Merlin Hanauer (2014) estimated the individual contribution of various mechanisms aff ecting poverty in and around Costa Rica's PAs. Th ey found that, on average, PAs reduced poverty and that two-thirds of the total reduction could be attributed to opportunities created by tourism.…”
Section: Experimental and Quasi-experimental Impact Evaluation Approamentioning
confidence: 99%